Optimization and field experiment of an adjustable device for sugar beet diggers - Wang, Fangyan (International Journal of Agricultural and Biological Engineering, 2021)
The harvesting operation, which affects the energy consumption and application performance, usually determines the harvesting effect and production quality of the crop. An adjustable sugar beet excavation device was designed to put the excavation equipment into practice by reducing harvest loss. The device is composed of an excavation disc, hub, pedestal, threaded rod, adjustable nut, boom, mounting seat, leak proof disc, etc. Through theoretical analysis, it was found that the excavation disc and the adjustment mechanism, which determine the excavation space and loading condition of the device, are important to the excavation device. Key parameters of the excavation disc were selected according to the growth status of sugar beet and the requirements of excavation space, with 340 mm as the radius of the excavation disc and 7.5° as the edge angle θ. The adjustment mechanism parameters were selected to change the operating parameters (inclination angle β and deflection angle γ) easily. Through the theoretical and experimental preliminary research, the key components structure and parameters of the excavation device were determined. By Central Composite Design (CCD) method, the regression equation was established, with rotation angle α, opening angle ε and excavation depth h as factors, and break rate, loss rate and excavation resistance as performance indexes. The influence of factors on performance indexes was estimated. The optimized parameter combination is: 35.37° of rotation angle, 15.08° of opening angle and 135.20 mm of the excavation depth. Experiments verified that the adjustable excavation device worked stably and achieved smooth excavation without congestion. The test indexes improved, with 0.6% of break rate, 1.1% of loss rate and 2312.8 N of the excavation resistance. This satisfied the requirement for beet harvest quality, and is roughly consistent with the optimization result. The research results can provide reference for the research on mechanized harvesting technology and equipment of sugar beet.Keywords: sugar beet, excavation, harvest, parameter optimizationDOI: 10.25165/j.ijabe.20211406.6667Citation: Wang F Y. Optimization and field experiment of an adjustable device for sugar beet diggers. Int J Agric & Biol Eng, 2021; 14(6): 68–74.